2011
DOI: 10.1021/es104216b
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Toxicity Effects of Silver Nanoparticles (NPs) on Drosophila melanogaster

Abstract: The use of nanoscaled materials is rapidly increasing, however, their possible ecotoxicological effects are still not precisely known. This work constitutes the first complex study focused on in vivo evaluation of the acute and chronic toxic effects and toxic limits of silver nanoparticles (NPs) on the eukaryotic organism Drosophila melanogaster. For the purpose of this study, silver NPs were prepared in the form of solid dispersion using microencapsulation method, where mannitol was used as an encapsulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(71 citation statements)
references
References 32 publications
7
64
0
Order By: Relevance
“…Especially, silver and gold nanoparticles show toxic effects on Drosophila fecundity and lifespan. [21][22][23]29 On the other hand, other studies reported that nanomaterials lack any significant adverse effects on Drosophila. For example, multi-walled carbon nanotubes at a concentration of 1,000 μg/g were shown to have no significant effect on developmental time or egg viability, 31 and single-walled carbon nanotubes at a concentration of 12-24 ppm during larval stage were reported to have no effect on pupal viability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, silver and gold nanoparticles show toxic effects on Drosophila fecundity and lifespan. [21][22][23]29 On the other hand, other studies reported that nanomaterials lack any significant adverse effects on Drosophila. For example, multi-walled carbon nanotubes at a concentration of 1,000 μg/g were shown to have no significant effect on developmental time or egg viability, 31 and single-walled carbon nanotubes at a concentration of 12-24 ppm during larval stage were reported to have no effect on pupal viability.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous reports on nanomaterial supplementation to flies, 15,25,[29][30][31] CNFs were suspended in ethanol (0.5, 5% wt), and stock CNF solutions were added to normal CSY or sucrose-yeast (SY) fly media (10% sugar, 10% instant yeast, 0.2% methyl-4-hydroxybenzoate, 0.5% propionic acid, and 0.8% agar) to make food with a final CNF concentration of 100 or 1,000 μg/mL (0.01 or 0.1% wt). Parent flies reared on normal CSY media were transferred to CNF-containing CSY food in order to lay eggs for 24 hours.…”
Section: Supplementation Of Cnfsmentioning
confidence: 97%
“…Nanotoxicity assessment studies have been previously conducted. Most of these studies use oral ingestion routes during third instar larval 32,[65][66][67][68] and adult stages 33,67,[69][70][71][72][73][74] to assess nanotoxicologic effects of several nanomaterials. Unfortunately, and because of the relatively small amounts of food intake during these stages, it is very difficult to accurately estimate actual amounts of ingested food.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several recent studies addressed the effect of silver nanoparticle toxicity, using oral ingestion as their administration routes, during third instar larva 32,68 and adult stages. 33,[69][70][71]73,74 If we consider that nanosilver has strong antimicrobial and antifungal properties, 80,81 together with the fact that Drosophila feeds mostly on microorganisms, particularly yeast, it is then possible to speculate that we may have confounding mortality effects arising from the unfavorable feeding conditions. Ingestion represents an important administration route, but more accurate screening tools are required.…”
Section: Discussionmentioning
confidence: 99%
“…Panacek et al 122 reported the acute and chronic toxicity effects of AgNPs on Drosophila. Acute toxicity assay indicated that half of the tested ies failed to nish their developmental cycle, and could not leave the pupae at a Ag concentration of 20 mg L…”
mentioning
confidence: 99%